Mechanisms of transverse relaxation of water in muscle tissue. (February 2022) - Anderssen, Kathryn E.; McCarney, Evan R.
Abstract: Nuclear magnetic resonance (NMR), and in particular transverse relaxation (T2 ), has been used to characterize meat and seafood products for decades. Despite many years of research, it is still not possible to reproducibly correlate the transverse relaxation of muscle foods to attributes that determine their quality and value. Instead of directly trying to interpret the T2 spectrum itself, typically chemometrics is used to try to relate the relaxation distributions to other measured properties on the sample. As muscle tissue is a porous medium, it is tempting to use equations developed to analyze other porous systems to provide a more direct, quantitative description of the tissue. However, the standard equations used to characterize porous materials have been developed for predominantly geological systems. This article discusses the foundations of transverse relaxation theory in porous media and the challenges that arise when attempting to adapt the equations to a biological system like tissue. One of the biggest issues that needs to be overcome before porous media theory can be reliably applied to characterize meat and seafood is to determine the source of relaxivity in the tissue. In order to better understand how the NMR signal originates, T2, diffusion, T1 -T2 correlation and T2 -T2 exchange experiments were performed on Atlantic cod ( Gadus morhua ) tissue in a variety of states (e.g. fresh, thawed, homogenized, etc.). In the literature, typically four T2 peaks are reported for meat and seafood samples. Results of this study indicate that the fastest relaxation peak is attributable to hydrogen within the protein itself and therefore arises from dipolar coupling. The T2B peak appears to belong to a type of bound water in protein called "buried water", and its relaxation stems from a combination of restricted motion and interaction with the hydrogen in the protein. For the T21 peak, attributed to fluid in myofibrils, the main relaxation mechanism is the interaction between water molecules and the hydrogen in myosin/actin matrix. The T22 peak arises predominantly from the interaction of water with dissolved protein in the sarcoplasm. An important finding from the study is the need to include both surface sinks and volume sinks in the interpretation of T2 relaxation results. Given these sources of the transverse relaxation in tissue, it is highly likely that changes to the T2 distribution that have been attributed to microstructural changes in the tissue are in reality due to a combination of changes in microstructure, surface relaxation and fluid properties. These findings aid in better interpreting T2 measurements in meat and seafood products and present a step towards a systematic approach for using transverse relaxation to quantitatively describe changes in tissue, with the ultimate aim of eventually predicting product quality and value from NMR relaxometry. Highlights: Multiple relaxation mechanisms exist for T2 relaxation in muscle tissue. Volume sinks play an important role in T2 relaxation in meat and seafood. Full T2 distribution should be used for analysis, not just peak location and area. T2 relaxation alone problematic to definitively describe chemical and structural changes. Advanced NMR sequences needed to properly characterize meat and seafood.